1993
DOI: 10.3109/02688699308995050
|View full text |Cite
|
Sign up to set email alerts
|

The anterior interhemispheric trephine approach to anterior midline aneurysms: Results of treatment in 72 consecutive patients

Abstract: We report the results of a prospective study of an anterior interhemispheric trephine approach in 72 consecutive patients with aneurysms of the anterior communicating artery (64 cases) and anterior cerebral arteries (eight cases). The salient features of the operative technique include a limited forehead crease incision, low anterior frontal midline trephine (4 cm), unilateral dural opening (2.5 cm), opening up of the anterior interhemispheric fissure and exposure of aneurysm and anterior cerebral vessels by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…12,18,19,27,35,48,49,56,57,69 Taking these series into consideration, without accounting for patients' preoperative status and despite the diversity of the criteria, the range of good results (GOS Scores 4 and 5) varied between 74 and 87.5%; excellent results rarely reached as high as 56.4% and the mortality rate lay between 3.5 and 6.8%. In our series, the proportion of excellent results was 65% in the overall population; however, the mortality rate was increased by 10.4%.…”
Section: Surgical Risk and Fundus Projectionmentioning
confidence: 96%
See 2 more Smart Citations
“…12,18,19,27,35,48,49,56,57,69 Taking these series into consideration, without accounting for patients' preoperative status and despite the diversity of the criteria, the range of good results (GOS Scores 4 and 5) varied between 74 and 87.5%; excellent results rarely reached as high as 56.4% and the mortality rate lay between 3.5 and 6.8%. In our series, the proportion of excellent results was 65% in the overall population; however, the mortality rate was increased by 10.4%.…”
Section: Surgical Risk and Fundus Projectionmentioning
confidence: 96%
“…These combined morbidity and mortality rates could be monitored during discussions of ACoA aneurysm management with the patient's family. A review of surgical series of patients with ACoA aneurysms, 12,18,19,27,35,48,49,56,57,69 revealed that the main cause of unfavorable outcome appears to be the initial SAH with its deleterious consequences, specifically, direct brain damage, hydrocephalus, or vasospasm-related ischemia. In our series, SAH was related to unfavorable outcomes in both microsurgically treated groups (1990-1995 and 1996-2000); it was responsible for approximately an 8% combined rate of morbidity and mortality among patients with a good preoperative status and approximately a 55% rate among those with a poor preoperative status.…”
Section: Surgical Risk and Fundus Projectionmentioning
confidence: 98%
See 1 more Smart Citation
“…A wide variety of approaches to the AComm region have been described,[79151820232533353738414547] and our description of the subfrontal approach only differs from other reports in subtle ways, but these subtleties have made big differences in our practice. All of the approaches provide appropriate exposure and achieve satisfactory results.…”
Section: Discussionmentioning
confidence: 97%
“…[257111820212325283236374448] It is important to emphasize that the purpose was not to create a minimally invasive exposure with limited access, but rather to tailor the pterional exposure and blend it with the subfrontal approach to this region to create a rapid, efficient and ample exposure for most AComm aneurysms. We present recent results in the patients treated through this approach because we are convinced that this exposure is similar to but more direct than the pterional approach, and offers an excellent option for rapid and adequate exposure and treatment of most AComm aneurysms.…”
Section: Introductionmentioning
confidence: 99%